Assistance in Manufacturing Photocells in Village Hall Lights as Efforts to Improve Lighting Effectiveness - Rosyidi, Mohammed Dawwam (OJS Universitas Muhammadiyah Gresik, 2024)
The lighting in the Sumberbendo village hall already uses LED lights and energy-saving lamps with varying capacities. Based on the results of observations, The system installed to operate the lights is still in operation manually through switch Which connected to light lighting. Pattern like This requires residents who live around the Village Hall to regularly devote their time For turn on And turn off light the. Condition in the field found there are still many PJU lights that have not been turned off even though the conditions are bright, and Not yet turned on although condition Already start dark, naturally matter This will affecting comfort and safety as well as the use of electrical energy that does not efficient. Based on the results of discussions with the Village, community service activities This will focused on modification light lighting on Hall Village with adding photocell technology so that the Village Hall lights operate can taking place in a way automatic . Beside That, done Also transfer knowledge.